2016
DOI: 10.1002/jcla.22080
|View full text |Cite
|
Sign up to set email alerts
|

The influence of vitamin C on the urine dipstick tests in the clinical specimens: a multicenter study

Abstract: Vitamin C was frequently found in clinical urine samples, and its concentration was higher in individuals undergoing medical check-ups. Urinary vitamin C can interfere with the urine dipstick results. This study gives useful information for predicting false-negative rates of urine dipstick tests caused by vitamin C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
0
9
2
Order By: Relevance
“…have detected AA in urine samples of 18.1% of patients of their hospital (group undergoing medical check-ups 23.1%, inpatients 16.3% and outpatients 17.6%). 20 These results indicate higher frequency than discovered in our study; however, the threshold for positivity in their study was lower (10 mg/dL) than in ours (20 mg/dL). When AA was detected in clinical urine samples, 42.3%, 10.6%, and 8.2% of the glucose, haemoglobin, and leukocyte esterase urine strip tests were rated as false negative, respectively.…”
Section: Discussioncontrasting
confidence: 71%
“…have detected AA in urine samples of 18.1% of patients of their hospital (group undergoing medical check-ups 23.1%, inpatients 16.3% and outpatients 17.6%). 20 These results indicate higher frequency than discovered in our study; however, the threshold for positivity in their study was lower (10 mg/dL) than in ours (20 mg/dL). When AA was detected in clinical urine samples, 42.3%, 10.6%, and 8.2% of the glucose, haemoglobin, and leukocyte esterase urine strip tests were rated as false negative, respectively.…”
Section: Discussioncontrasting
confidence: 71%
“…Ascorbic acid (vitamin C) is frequently found in clinical urine samples and can interfere with the dipstick results . Previous studies have demonstrated that even modest ingestion of vitamin C supplements (350‐1000 mg/d) can cause high concentration of vitamin C in urine which interferes with dipstick determination of glucose and hemoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, all subjects who ingested a dose of 350 to 1000 mg of vitamin C per day had concentrations of 25 mg/dL or more of vitamin C in urine . Most of the studies which investigated ascorbic acid impact on urinalysis were performed 10‐20 years ago, which makes our investigation even more important.…”
Section: Discussionmentioning
confidence: 99%
“…Diets rich in fruit and vegetables have linked with a reduced risk of chronic disease (Woodside et al, 2017). For healthy, pregnant women need to consume amounts of fruits and vegetables every day, which happen to contain lots of vitamin C. That's why our data showed that the incidence of urinary vitamin C was 27.7% of 34,279 urine samples, which was higher than 18.1% of 5,006 routine urinalysis specimens (Lee et al, 2017). Vitamin C's impact in chemical tests is widespread, not only in urine chemical tests but also in serum biochemical tests.…”
Section: Discussionmentioning
confidence: 67%
“…Though Wonmok Lee etc. (Lee et al, 2017) showed that vitamin C interferes with hemoglobin and leukocyte esterase results. Vitamin C can cause the urine dipstick result was two or more grades lower than the urine sediment result.…”
Section: Discussionmentioning
confidence: 99%